2009
DOI: 10.1371/journal.pgen.1000786
|View full text |Cite
|
Sign up to set email alerts
|

Comparative ICE Genomics: Insights into the Evolution of the SXT/R391 Family of ICEs

Abstract: Integrating and conjugative elements (ICEs) are one of the three principal types of self-transmissible mobile genetic elements in bacteria. ICEs, like plasmids, transfer via conjugation; but unlike plasmids and similar to many phages, these elements integrate into and replicate along with the host chromosome. Members of the SXT/R391 family of ICEs have been isolated from several species of gram-negative bacteria, including Vibrio cholerae, the cause of cholera, where they have been important vectors for dissem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
439
1
9

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 249 publications
(466 citation statements)
references
References 69 publications
17
439
1
9
Order By: Relevance
“…ICEs appear to be major players in the horizontal transfer of genetic material between bacterial species, as they carry genes required for their own excision and transfer to recipient bacteria (113). This is exemplified in Salmonella by SPI-7, an ICE that is present in Salmonella but also among a variety of other Enterobacteriaceae (114).…”
Section: Impact Of Horizontal Gene Transfer On Genome Evolution and Hmentioning
confidence: 99%
“…ICEs appear to be major players in the horizontal transfer of genetic material between bacterial species, as they carry genes required for their own excision and transfer to recipient bacteria (113). This is exemplified in Salmonella by SPI-7, an ICE that is present in Salmonella but also among a variety of other Enterobacteriaceae (114).…”
Section: Impact Of Horizontal Gene Transfer On Genome Evolution and Hmentioning
confidence: 99%
“…Together with other "R factors," R391 was initially identified in the early 1970s as a plasmid conferring resistance to kanamycin and was defined as the prototypical representative of the "IncJ" incompatibility group of plasmids, which included other "R factors" such as R997 from an Indian Proteus mirabilis isolate as well as the socalled plasmids pMERPH from Shewanella putrefaciens and pJY1 from V. cholerae O1 (for a review, see reference 28). More than two decades after the discovery of R391, an accumulation of evidence based on the comparison of integration sites and conservation of a large set of nearly identical genes confirmed that SXT as well as all of the "IncJ elements" belong to the same family of ICEs, referred to as the SXT/R391 family (29,30,31,32).…”
Section: The Sxt/r391 Familymentioning
confidence: 99%
“…SXT/R391 ICEs are major contributors to the spread of multidrug resistance in V. cholerae (27,31,32). In fact, most SXT/R391 ICEs found in clinical isolates confer resistance to sulfamethoxazole and trimethoprim, two commonly used antibiotics.…”
Section: The Sxt/r391 Familymentioning
confidence: 99%
“…Another effect of SOS induction is the derepression of genes involved in the single-stranded transfer of integrating conjugative elements (ICEs), such as SXT from V. cholerae, which is a ϳ100-kb ICE that transfers and integrates the recipient bacterium's genome, conferring resistance to several antibiotics (11). Moreover, different ICEs are able to combine and create their own diversity in a RecA-dependent manner (i.e., using homologous recombination, which is also induced by SOS) (50,156). As for R plasmids, SXT transfer was observed to induce SOS in V. cholerae.…”
Section: Single-stranded Dna Stress and Horizontal Transfermentioning
confidence: 99%